The functional structure of the academic year at higher education institutions in the United States of America and at South African technikons, with particular reference to the communication sciences - Denys Rhoodie (Communicare)
The decision to undertake this study was based on the belief that both time management and the time-allocation framework of the academic year of South African technikons, specifically as regards journalism, public relations and mass communications programmes, needs substantial organisational and functional restructuring to come to terms with radically changed societal, economical, political and educational realities. Legitimacy, quality assurance and resources are the three main components of an educational system. Time is a vital resource as well. The major thrust of the study was to ascertain at first-hand how the American academic calendar works in practice and whether it offers distinct advantages that could practically and in accordance with current legislation and policy be introduced in the academic calendar of South African technikons in general, and communications programmes in particular. This included looking at continuous student assessment and summative final examinations insofar as they impact on the use of academic time for teaching. In conclusion, the study proposes the creation of a new time mould which will result in a more effective use of existing academic time and also provides a number of additional benefits and advantages to both student and teacher/instructor